Manipulative Behavior : The Main Female Character in Movie “Gone Girl” - Sutrisno, Bejo; Ayuningsih, Diana; Rachmawati, Budi (STIBA IEC JAKARTA, 2025)
The aim of this research is to analyze and find out tactics of manipulators in a movie entitled Gone Girl. This movie tells about a Missouri couple who had a great life, but it all changed when their 5th wedding anniversary occurred. The story begins with Nick Dune’s wife, the Amazing Amy, has gone missing. Along with the process of investigation, it became blurred between Nick’s story and the investigation result. Nick suspected of killing his wife and he struggled for convincing the media. The writer used the qualitative method in this research. The researcher used the theory of manipulation behavior and emotionally abusive relationship. This analysis focuses on the main female character’s manipulative behavior that is shown from the storyline of the movie. The findings of this research are the tactics used by Amy are mostly lying and acting like a victim. She can make the situation seem that she is the victim being tortured by the people around her